Integrated method for planning waste management based on the material flow analysis and life cycle assessment - Bendiuh, Vladyslav; Markina, Liudmyla; Matsai, Nataliia; Kyrpychova, Iryna; Boichenko, Sergii; Priadko, Serhii; Shkilniuk, Iryna; Komarysta, Bohdana; Yermakovych, Iryna; Vlasenko, Oleh (Eastern-European Journal of Enterprise Technologies, 2023)
This paper gives a solution to the problem of improving a solid waste management system through the integration of two systemic methodologies: material flow analysis and life cycle assessment. The proposed method serves to assess the effectiveness of the implementation of various waste management measures. The study was carried out with the detailing of the anaerobic digestion process since it is this recycling technology that plays a key role in reducing the amount of waste along with the production of renewable energy and in reducing the adverse effects on the external environment. Simulation of changes in waste properties in a certain processing sequence was carried out in order to obtain reliable information for further optimization of the system. The proposed modeling of waste treatment processes based on their constituent equations made it possible to adequately reflect the impact of changes in working conditions on all subsequent output flows. The analysis of material flows for an enterprise of mechanical and biological treatment of waste is presented and the use of the model in the context of the process of anaerobic digestion of household waste is illustrated. It was found that anaerobic digestion potentially makes it possible to obtain 4.1 Gj of biogas energy from 1 HSW, which corresponds to 460 kWh of electricity and 2060 MJ of heat. The developed method is based on a combination of analysis of material flows and life cycle assessment. The method acts as a tool for comparing alternative technologies and waste management scenarios. In the future, it can serve to support waste management decisions at both the strategic and operational levels